The Effect of Oral Tizanidine on Bleeding and Quality of Surgical Field During Endoscopic Sinus Surgery - A Mahoori (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Intraoperative bleeding during endoscopic sinus surgery compromises the surgeon s vision for surgery at the surgical field. Since tizanidine causes contraction of peripheral blood vessels and hypotension, which together reduce blood flow to nasal mucosa, this study was performed to evaluate the effect of oral tizanidine on the quality of vision at the surgical field during endoscopic sinus surgery. METHODS: This double-blind clinical study was performed on 60 patients. Patients were randomly divided into two groups by computer randomization software (2.0) and received 6 mg tizanidine and placebo before the surgery. During the operation, the quality of the operation field was evaluated and scored by the surgeon based on Boezaart scale. Pain score in recovery and 6 hours after surgery and intraoperative hemodynamic parameters were assessed. FINDINGS: The quality of the surgical field based on the Boezaart scale was significantly better in the group receiving tizanidine (p=0.04). Pain score in recovery was 2.83±1.17 in the case group and 4.53±1.56 in the control group (p=0.001). Pain score 6 hours after surgery in the case group was 3.23±1.22 and in the control group was 4.13±1.33 (p=0.008). Mean arterial blood pressure (p=0.03) and heart rate (p=0.19) during surgery were lower in the tizanidine group. CONCLUSION: The results of the study showed that tizanidine as a perioperative medication before endoscopic sinus surgery improves the quality of vision at the surgical field and provides a better hemodynamic profile for patients.